EFEKTIVITAS MODEL PROJECT BASED LEARNING TERHADAP HASIL BELAJAR MATERI IPAS DI SDN GAYAMSARI 01 - Ardanti, Betharia Mei; Fine Reffiane; Fajar Cahyadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is based on the limited variety of learning models applied in educational practices in elementary schools. The main objective of this research is to ascertain whether the application of the Project Based Learning model helps improve students' learning outcomes. To obtain the data needed in this study, pre-experimental quantitative research with a one-group pretest-posttest design was used. The findings showed a significant increase, which can be seen through the comparison of pretest and posttest scores. The average posttest score was 85.95> from the average pretest score of 60.00. Furthermore, testing using paired samples test statistical analysis showed a t test value of 17.43 and a t table value of 2.086. This means that t count is greater than t table so H0 is rejected and Ha is accepted. The average value of learning outcomes shows an increase and a significant influence after the application of this learning model. Therefore, the conclusion is that the Project Based Learning model is proven to be effective and capable of improving the learning outcomes of fourth-grade students of SDN Gayamsari 01.